AI-Supported Outcome-Based Learning: Integrating ChatGPT Interaction to Enhance Students’ Critical Thinking in Educational Research - Nur Azmi Rohimajaya; Ledy Nur Lely; Welliam Hamer (Journal of English Language Studies, 2026)
This study explores how Outcome-Based Education (OBE) is integrated with Artificial Intelligence (AI) tools, particularly ChatGPT, and focuses on students’ perceptions of its influence on critical thinking in an Educational Research course. Despite the widespread global adoption of the OBE framework, empirical research remains limited regarding how ChatGPT is systematically integrated into OBE through constructive alignment and how such integration is implemented in classroom practice, particularly in Indonesian higher education. This study used a qualitative case study design. Sixteen seventh-semester students from the English Education Department at Universitas Mathla’ul Anwar Banten, Indonesia, participated in the study. Data were collected from three sources: classroom observations, open-ended questionnaires, and semi-structured interviews. Six participants were purposively selected for the interviews. The findings suggest that integrating ChatGPT into the OBE framework was perceived as supporting students’ analytical thinking, self-reflection, and problem-solving. Students reported valuing the immediate feedback provided by ChatGPT, which encouraged deeper inquiry aligned with the intended OBE learning outcomes. The study also identified several challenges, including ethical concerns, the risk of overreliance on AI, and differences in digital literacy. Overall, the findings indicate that an AI-assisted OBE approach may support structured and reflective learning in higher education when accompanied by clear ethical and pedagogical guidelines for responsible AI use. In practice, lecturers should align the use of ChatGPT with clearly defined learning outcomes and ethical guidelines.